Human Resource Accounting For Implementation In Actual Organizations: Recognizing and Appreciating the Value of Employees in Human Resource Accounting (Journal of Advances and Scholarly Researches in Allied Education, 2015)
It is highly complicated in the today’s market find wellknowledge, coached, and highly motivated people. Human resource is one of themost important back office operations of any organization or business. Theirskills, creativity, ability human cannot be replaced by machines. We can loseefficiency in work if no qualitative people. At all levels and areas of thebusiness or firm human efficiency is required with machine efficiency. Humancan work without machine but machine can’t. Hence, industry like advertisingand direct marketing for instance human talent is more valuable among otherelse. No machine can ever come up with a unique advertising idea without thehuman input. Thus companies must learn to recognize and appreciate the value oftheir employees. It is worth and capital investments.